Form Of Legal Protection For Children Of Sexual Harassments In The Namlea State Court, Maluku - Fauziah Rahawarin; Husin Wattimena (IHSA Institute, 2022)
This article aims to examine forms of legal protection for child sexual abuse perpetrators in the Namlea District Court in Maluku. This type of research is normative-empirical research. The data collection techniques of this research are literature study, documentation study, and interviews. There are two research data, namely primary data and secondary data. Primary data is the text of the law related to the criminal law system and child protection. Secondary data is data supporting primary data such as books and expert opinions. The data analysis process includes stages (1) word grouping, (2) data reduction, (3) data transcription, and (4) data interpretation. The results of this study indicate that the form of protection for child perpetrators of sexual abuse is resolved through a restorative justice approach in accordance with Law No. 11 of 2012 concerning the juvenile criminal justice system. In addition, diversion efforts must be carried out starting from the stage of investigation, prosecution, to trial in order to provide protection for children holistically.